Implementation of event management through communication, leadership, and time management training for students of SMA Al Hilal Ambon - M Sahrawi Saimima; Anna Wally Burangasi; Saleha Wally; Nur Anisa Syawal; Saiful Rumatiga (Balai Diklat Keagamaan Ambon, 2025)
Event management is a professional activity that brings together a group of people to carry out specific tasks or events. This activity aims to train students in managing activities related to the theme of training, thereby improving their communication, leadership, and time management skills. The method used is service learning, which involves the direct participation of students from the MPI FITK UIN AM Sangadji Ambon Study Program as the organising committee, utilising a participatory approach through the delivery of interactive materials and panel discussions. The implementation of the activity involved 11 students in grades X and XI of Al Hilaal Ambon High School. The results of the activity showed that students were trained in the courage to speak in public, the importance of leading and managing groups, and were given tips on managing time related to their academic activities. The results obtained by students in managing activities through the application of event management stages, ranging from research, design, planning, coordination, and evaluation, show that there are obstacles in the coordination aspect. It is due to a change in the implementation schedule, where activities that were originally scheduled together must be carried out earlier than the planned target. However, this activity provides dual benefits, namely, strengthening students' soft skills and improving student competence in managing educational events professionally.